Hubungan Usia, Tingkat Pengetahuan, dan Riwayat Penggunaan Alat Kontrasepsi dengan Pemilihan Alat Kontrasepsi pada Penderita HIV/AIDS - Susanti, Susanti; Sujianti, Sujianti; Lestari, Yogi Andhi (Jurnal Bidan Cerdas, 2021)
Introduction: In couples, one of whom is diagnosed with HIV, generally the partner is emphasized not to have unprotected sex. This includes the selection of contraceptive methods for women with HIV/AIDS to achieve their reproductive goals. Objective: to analyze the relationship between age, education level, and history of contraceptive use with the choice of contraceptive method in women with HIV/AIDS. Methods: This study uses a descriptive correlative design using Fisher test analysis with a total sample of 20 people who meet the criteria. Results: the relationship between age and current contraceptive use with a p value of 0.241, a history of contraceptive use and current contraceptive use with a p value of 1.00, and the level of knowledge with current contraceptive use with a p value of 0.122. Conclusion: there is no relationship between age, history of contraceptive use, level of knowledge, and current use of contraceptives with p value > 0.005.